Understanding the caking behavior of amorphous jujube powder by powder rheometer. (March 2019) - Addo, Keren Agyekumwaa; Bi, Jinfeng; Chen, Qinqin; Wu, Xinye; Zhou, Mo; Lyu, Jian; Song, Jianxin
Abstract: Chinese jujube, rich in nutritional and nutraceutical values, is mostly preserved by drying in powder form. However, jujube powder is at amorphous state and prone to caking which has a negative impact on product manufacturability and quality. Effects of five different drying methods on caking of jujube powders were quantified by using the powder rheometer. In general, non-homogeneous caking of jujube powder was observed. Drying methods showed significant effect on the caking of jujube powder, powder dried by freeze drying and instant controlled pressure drop drying showed highest and lowest crust strength (622 and 170 mJ/g) at 25ᵒC, 75% RH for 5 h, respectively. Strength of caking increased with rising of RH and load. Temperature and time show coupled effect on powder caking and higher temperature could significantly accelerate caking strength of powders. When the moisture content of jujube powder was over 0.066 g/g at 25ᵒC, glass transition would happen. Structure of jujube powder would change from "amorphous glassy" to "amorphous rubbery". Caking of particles was mainly due to sinter bridge formation and fructose was one of the main contributor to caking of jujube powder. Highlights: Non-homogeneous caking of jujube powder was observed during storage. Strength of caking increased with rising of relative humidity, temperature and load. Glass transition of jujube powder will happen at 25 ᵒC when water content is over 0.066 g/g. Structure of powder changed from "amorphous glassy" to "amorphous rubbery" after caking. Powder rheometer is an effective method for assessment caking of jujube powders.